Vampires bats - Bross, Eric; Morgan, Christopher; Tanner, Jill; von Zerneck, Frank; Prochilo, Doug ([Culver City, California] : Sony Pictures Television, 2005)
In Mercier, Louisiana, the freshmen friends of the Tate University Jason Ortiz, Aaron and Eden go to an underground party in the woods nearby the local cemetery. They drink the punch spiced with ecstasy and completely drugged, Jason is attacked and killed by violent bats. When the police finds the body, they arrest Aaron and Eden as prime suspects. However, their biology professor Maddy Rierdon sees the corpse and advises that the youngster had been actually bitten by animals
Title from title screen
Special features: Theatrical trailers
Executive producers: Randy Sutter, Jill Tanner, Frank von Zerneck ; associate producer: Kimberly C. Anderson, Laurence Ducceschi
Cast: Lucy Lawless, Dylan Neal, Liam Waite, Timothy Bottoms, Craig Ferguson, Brett Butler, Tony Plana, Jessica Stroup, Jerrod Paige, Arnie Pantoja
DVD format
Dolby digital
Keywords: Vampire bats -- Drama; Suspense in motion pictures